Inovasi Aplikasi Online Green Waqf Berbasis Blockchain Guna Pendanaan Produktivitas Tamanu Sebagai Upaya Pelestarian Lingkungan - Sukaina, Iin Dwi; Zahidah, Hana Fitria; Arifian, Falsa Dzaky (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2022)
Various parties are required to innovate renewable energy to support life in the future. One of the innovations to support renewable energy is utilizing the tamanu plant (Calophyllum inophyllum). Tamanu plants can reduce carbon emissions and can be processed into cosmetic ingredients and medicines that have the potential to create a sustainable business. However, the development of industry requires large costs so adequate financing is needed. One of the financing models is green waqf in the form of money by utilizing blockchain. With blockchain storage technology, data can be maintained properly. Therefore, this research aims to describe an application innovation called